Examining the relationships between environmental barriers and leisure in community-dwelling individuals living with stroke. (April 2019) - Tang, Ada; Sun, Billy; Pang, Marco YC; Harris, Jocelyn E
Objective: To characterize environmental barriers to leisure participation among individuals living with stroke; examine relationships between environmental barriers and leisure interest and satisfaction; and investigate participant factors associated with the perception of environmental barriers. Design: Survey. Setting: Community. Participants: Convenience sample of 51 community-dwelling adults less than six months post stroke. Interventions: Not applicable. Main outcome measure(s): Craig Hospital Inventory of Environmental Factors-Short Form. Results: Physical and structural environmental barriers were reported as the most frequent and large barrier to leisure participation ( n  = 26 (51%) rated as "monthly or more, " n  = 12 (24%) rated as "big problem"). While attitude and support and policy barriers were not as commonly encountered, participants labeled these as "big problem(s)" (attitude and support n  = 6 (12%), policy n  = 7 (14%)). The presence of depressive symptoms was associated with the frequency in which attitudinal and support (rho = 0.50, P  < 0.001), physical and structural (rho = 0.46, P  < 0.001), and service and assistance (rho = 0.28, P  = 0.04) barriers were reported, as well as magnitude of attitude and support barriers (rho = 0.48, P  < 0.001). In multivariable regression analysis, depressive symptoms and walking capacity explained 21% of the variance of the frequency of attitude and support barriers ( P  = 0.004), where depressive symptoms was an independent correlate ( P  = 0.004). No other factors were associated with environmental barriers to leisure participation. Conclusion: Individuals with stroke report frequent and large physical and structural environmental barriers to leisure participation, which may be associated with the presence of depressive symptoms.